Anterior segment parameters measured in young healthy cats using a rotating Scheimpflug camera. (5th March 2019) - Verneuil, Marc; Marsot, Maud; Ruchon, Charly
Abstract: Objective: The purpose of this study is to measure parameters of the anterior segment of normal feline eyes using a rotating Scheimpflug camera in young and adult cats. Procedure: Sixteen domestic short‐haired (DSH) healthy cats (seven castrated males and nine spayed females) with a mean age of 17 months (SD = 3.5) were anesthetized. Cats were considered immature and adults if they were < or ≥12 months of age, respectively. The keratometric values, the anterior chamber depth (ACD), and central corneal thickness (CCT) of the right eye of each animal were measured using a Pentacam Oculus topographer. The repeatability of the measures was assessed by calculating the coefficient of variation of the successive measures in cats (five repetitions per cat). We performed an ANOVA to test the effect of age on the parameters measures. Results: The mean CCT and ACD were 601.97 ± 38 μm and 5.27 ± 0.04 mm, respectively. No significant differences were observed between adult and young cat's measures. The average keratometric value was 39.6 ± 0.3 D. The mean average cylindrical error was 2.48 ± 0.35 D (43.75% "against‐the‐rule" astigmatism and 43.75% "oblique" astigmatism). Conclusion: The Oculus Pentacam under clinical conditions give CCT and ACD values very similar to those reported in previous studies. Corneal astigmatism measures were markedly elevated (>2 D). Further studies with a larger population of cats of various breeds and ages are needed to confirm or refute these results, using a rotating Scheimpflug camera.